The impact of smoking on response to tumor necrosis factor-? inhibitor treatment in patients with ankylosing spondylitis - Tugsal, Handan Yarkan; Kenar, Gokce; Can, Gercek; Capar, Sedat; Zengin, Berrin; Akar, Servet; Onen, Fatos (Tubitak Scientific & Technological Research Council Turkey, 2023)
Background/aim: To investigate the impact of smoking on disease activity, treatment retention, and response in patients with ankylosing spondylitis (AS) treated with their first tumor necrosis factor-alpha inhibitor (TNFi). Materials and methods: AS patients who started their first TNFi treatment for the active axial disease (BASDAI >= 4) from TURKBIO Registry were included. Treatment response of smoker (current and ex-smokers) and nonsmoker (never smoker) patients were primarily evaluated as achievement of BASDAI50 or improvement in BASDAI at least 20 mm at 3 months and 6 months compared to baseline. Results: There were 322 patients with AS (60% male, 59% smoker, mean age: 38.3 years). The median follow-up time was 2.8 years (Q1-Q3: 1.3-3.8), and disease duration was 3.5 years (Q1-Q3: 0.7-8.2). Smokers had male predominance (p < 0.001), lower ESR (p = 0.03), higher BASDAI (p = 0.02), BASFI (p = 0.05), HAQ-AS (p = 0.007), and ASDAS-CRP (p = 0.04) compared with nonsmokers at baseline. In the multivariate analysis, male gender [OR 2.7 (95%CI 1.4-5), p = 0.002], and concomitant conventional synthetic disease-modifying antirheumatic drug use [OR 2.4 (95%CI 1.1-5.2), p = 0.03] were associated with better treatment response. There was an association of male gender [HR 2.4 (95%CI 1.6-3.7), p < 0.001], older age (>= 30years) [HR 1.8 (95%CI 1.1-2.8), p = 0.01], and response to treatment [HR 1.8 (95%CI 1.2-2.9), p = 0.008] with better treatment retention. No impact of smoking status was found on treatment retention and response in univariate and multivariate analyses. Conclusion: This study suggested that smoking was associated with poorer patient-reported outcomes in biologic naive AS patients initiating their first TNFi treatment, but it had no impact on the TNFi treatment response and retention rate.
Keywords: Ankylosing spondylitis; smoking; tumor necrosis factor-alpha inhibitor; treatment response; registry